Demumentalization of the military dictatorship: an experience report from an exchange program in the memory centers and concentration camps of Germany and Poland - Mourao, Alexandre de Albuquerque (Revista do Colóquio, 2025)
This text reports on the exchange program "Demonumentalization of the Dictatorship," conducted by the Coletivo Aparecidos Políticos (Fortaleza, CE), in Germany and Poland. The objective was to use the consolidated European social memory of Nazism (including visits to the Auschwitz and Dachau concentration camps) to reflect on the struggle against the glorification of the Brazilian military dictatorship (1964-1985) and the rise of the current far-right. The experience revealed that, even in countries with a strong "culture of memory," the resurgence of extreme populism is a reality. It concludes that memory should be treated as a continuous emergency warning against hatred and historical repetition, as Primo Levi emphasized.